If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (10 + -2x)(8 + -2x)(x) = f(x) Reorder the terms for easier multiplication: x(10 + -2x)(8 + -2x) = f(x) Multiply (10 + -2x) * (8 + -2x) x(10(8 + -2x) + -2x * (8 + -2x)) = f(x) x((8 * 10 + -2x * 10) + -2x * (8 + -2x)) = f(x) x((80 + -20x) + -2x * (8 + -2x)) = f(x) x(80 + -20x + (8 * -2x + -2x * -2x)) = f(x) x(80 + -20x + (-16x + 4x2)) = f(x) Combine like terms: -20x + -16x = -36x x(80 + -36x + 4x2) = f(x) (80 * x + -36x * x + 4x2 * x) = f(x) (80x + -36x2 + 4x3) = f(x) Multiply f * x 80x + -36x2 + 4x3 = fx Solving 80x + -36x2 + 4x3 = fx Solving for variable 'x'. Reorder the terms: -1fx + 80x + -36x2 + 4x3 = fx + -1fx Combine like terms: fx + -1fx = 0 -1fx + 80x + -36x2 + 4x3 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-1f + 80 + -36x + 4x2) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-1f + 80 + -36x + 4x2)' equal to zero and attempt to solve: Simplifying -1f + 80 + -36x + 4x2 = 0 Reorder the terms: 80 + -1f + -36x + 4x2 = 0 Solving 80 + -1f + -36x + 4x2 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| -8+x=4x+1 | | cos+2sec=-3 | | -16=2(1-5x)+4 | | x+3.5=8.5-9x | | 10x-5(x-2)=30 | | 7-4x-3x-5=6x+1+2x-3 | | =(4x-3)(2x+7)-(4x-3)(6-x) | | 3(a+b)+2(a-b)= | | 0.1x+0.25x=20.65 | | -3=153 | | 2v-26=-9(v+9) | | 9x-10=2x+6 | | 6(2.5+3x)-13x=8x-24 | | 16n-6-9n=43-2n+5 | | -6(2-4n)+5=161 | | y(y+5)+2(y-3)= | | 5(3x-4)=32+2x | | 336=6(-6x+8) | | 34-3x=6x+7 | | 0.66x-10=0.5x-8 | | 12t=-123 | | 364=-5(8n-8)+4 | | 2f(x)=4x-2 | | 2x-b=3 | | 0.2=10 | | 4r-4+8=-16 | | 2(x-6)-4x=-14 | | 4+3b+1=8 | | 84=2x+2x^2 | | 12=1-6n-5n | | 72=(a*10)+(a*2a) | | 5(t-3)-3(2-t)= |